question 6 please if anyone knows
Attachments:
![](https://hi-static.z-dn.net/files/d2a/6482ef6b297c3ae15d215b72e9dc9a3b.jpg)
Answers
Answered by
0
The solution is in this attachment .Hope it will help you.
Attachments:
![](https://hi-static.z-dn.net/files/d14/bf11f72e4dfc04cbb2ed182790322fd4.jpg)
Answered by
0
take sec^2(theta) common and you'll be left with,
sec^2(theta){ sec^2(theta) - 1}
we know that,
sec^2(theta) = 1+tan^2(theta)
by using the above identity,
= {1 + tan^2(theta)} {1 + tan^2(theta) - 1}
= [ 1+ tan^2(theta)][tan^2(theta)] ;)
sec^2(theta){ sec^2(theta) - 1}
we know that,
sec^2(theta) = 1+tan^2(theta)
by using the above identity,
= {1 + tan^2(theta)} {1 + tan^2(theta) - 1}
= [ 1+ tan^2(theta)][tan^2(theta)] ;)
Similar questions